Effect of texture modifiers on the physicochemical and sensory properties of dried fufu - Adebowale, A.A.; Sanni, Lateef O.; Awonorin, S.O. (SAGE Publications, 2005)
Glycerol monostearate (GMS) and monoglyceride phosphate (MGP) were added to fufu flour at different levels (0.5%, 1.0% and 1.5%) in hydrated and powdered form. There were evaluated the effects of those additives on physicochemical and sensory properties of dried fufu. Addition of GMS and MGP had a significant effect on the swelling power, solubility, pasting properties and sensory quality of fufu flour. Results obtained were: Dispersibility (69%-70.33%), water absorption index (WAI, 47.7%-54.4%), least gelation concentration (LGC, 4.67%-6.67%) and water absorption capacity (WAC, 119.3%-136%) for the fufu flour treated with GMS and MGP. Solubility of the samples mixed with the powdered form of the modifier ranged between 23.2% and 31.7%, while that of the samples mixed with the hydrated form of GMS and MGP ranged between 5.3% and 12.7%. The pasting time varied between 8.25min and 18.50min, fufu flour mixed with 1.5% GMS powder had the lowest value while that mixed with 1.0% MGP powder and 0.5% hydrated MGP recording the highest value. Pasting temperature ranged from 67.00°C to 72.00°C, with flour mixed with 1.0% hydrated GMS and 0.5% GMS powder having the lowest and highest value, respectively. The highest value of peak viscosity (762.50BU) was recorded by fufu flour containing 1.0% hydrated GMS. The lowest value of starch stability (255.50BU) was recorded by fufu flour without modifier while the highest value (499.00BU) was recorded by fufu flour containing 0.5% GMS powder. There were significant differences (p 0.05) in the sensory qualities except for colour of fufu flour samples. The overall quality index (OQI) comprised between 5.24 and 6.01, fufu sample containing 0.5% hydrated GMS had the lowest OQI and that containing 1.0% hydrated MGP the highest OQI. Addition of 0.5% texture modifier to dried fufu may be economically feasible according to the estimated cost of production.